The Afterlife of John Brown - Herrington, E.; Herrington, E. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2005)
"An examination of the influence--however contested--of John Brown of the Harper's Ferry Rebellion on the national narrative of the United States"--Amazon.com.